The redispersion behaviour of Pt on the surface of Fe2O3. Issue 31 (9th March 2016) - Li, Jingwei; Zhang, Yibo; Yi, Ting; Zhang, Zeshu; Miao, Zhenzhen; Sun, Liwei; Zhang, Zhendong; Yang, Xiangguang
Abstract : Pt could be redispersed on the surface of Fe2 O3 with alternating treatment under oxidative and reductive atmospheres. Abstract : The redispersion behaviour of Pt on ferric oxides under cyclic oxidizing/reducing conditions was observed and studied using several analysis techniques. Pt in a Pt/Fe2 O3 catalyst sintered after treatment under a single oxidative or reductive atmosphere at 600 °C and the average size of the Pt nanoparticles increased from the original 3.2 nm to 6.8 and 14.6 nm, respectively. In contrast, the average size decreased to 1.1 nm when the catalyst was treated under an alternating oxidizing and reducing atmosphere. It is proposed that the Pt–O–Fe bond formed under an oxidative atmosphere and the related defects or oxygen vacancies formed under a reductive atmosphere play an important role during the redispersion of Pt. In addition, the effect of temperature on the redispersion of Pt is also noted and discussed.